(untitled) (Forum Penelitian Agro Ekonomi, 2023)
During 2016–2020, there has been a decline in the number of workers in the agriculture sector. Negative perceptions make the agriculture sector no longer promising and are slowly being abandoned, especially by the younger generation. This study analyzed the problems and the efforts to attract and develop millennial farmers. This study is a qualitative study using a qualitative approach with descriptive analysis of the available secondary data. The results show that youth involvement is lower in the agriculture sector. Several factors, such as wage or income levels, unsupportive policies and lack of access to technology, self-development, and capital, cause it. Therefore, it is necessary to regenerate farmers through the development of millennial farmers by attracting the younger generation’s interest in the agricultural profession, developing modern agriculture, supporting government policies, agricultural vocational education, and easy access to agriculture.